Desenvolvimento de aços com alto nível de limpidez - Carneiro, Carlos André Ruy (2024)
The physico-chemistry of steel fabrication and solidification is so complex that it is impossible to produce completely defect-free products. For this reason, it is necessary to understand and control all the factors that can influence the quality of the product and processes. The occurrence of defects (internal and/or superficial) interferes with the productivity of the process, as it can lead to the scrapping of the slab and/or the introduction of another step to remove these defects, in addition to causing refusals in the laminated product. In all cases, the main implication is increased operating costs. The development of products with the absence of defects involves the development of steelmaking processes aimed at steels with high levels of cleanliness. The development of cleanliness evaluation techniques and the full understanding of the metallurgical fundamentals and operational procedures that impact the cleanliness of Ultra Low Carbon steels with automotive application and steels with the need for globulization of inclusions will be the focus of this thesis. The challenges consisted of defining refining and casting process parameters that ensure optimal levels of cleanliness based on sliver results in the product for Ultra Low Carbon steels and clogging index for steels using the inclusion globulization process. The results positioned the Steelmaking plant as a reference in quality in Ultra Low Carbon steels with cleanliness levels higher to the best market references. Also noteworthy are the process optimizations, also related to cleanliness, which allowed the significant reduction of clogging in continuous casting in steels with calcium addition. Different practices and procedures were developed and implemented, allowing the continuous development of the process, such as the development of techniques for evaluating cleanliness that will allow the Steelmaking plant to predict and act on processes in order to optimize quality according to the customer's needs; definition of relationships between sliver, total oxygen and inclusion count for Ultra Low Carbon steels; Process index mapping and knowledge creation for the organization